Role of cetrorelix in the prevention and treatment of ovarian hyperstimulation syndrome: a prospective case control study - V. Mishra, Vineet; Rane, Priyanka H.; Aggarwal, Rohina S.; Choudhary, Sumesh; Chhetry, Manisha; Solanki, Smit B. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Ovarian hyperstimulation syndrome (OHSS) has intrigued clinicians for many years because of its devastating consequences. As an iatrogenic condition resulting from elective ovarian stimulation in the quest for pregnancy, the need to completely prevent the syndrome is evident. Gonadotropin releasing hormone (GnRH) antagonist Cetrorelix has found to be effective in treatment of OHSS and some studies have found it to be helpful in prevention of this condition. Hence, we designed a hospital-based study to investigate the effect of Cetrorelix in preventing and treating OHSS in in-vitro fertilization – embryo transfer (IVF–ET) patients at risk of OHSS undergoing long and short protocol. Methods: The study includes total 102 patients undergoing controlled ovarian stimulation COS for IVF/ICSI. All cases were stimulated using long and short protocol. Depending on whether a GnRH antagonist was given after ovum pick-up (OPU) the patients were divided in two groups: Cetrorelix (antagonist) group (n=51) and control group (n=51). The study group was treated with Cetrorelix 0.25 mg for 5 days commencing on the day of ovum pick up. Results: Incidence of mild OHSS was significantly higher (p=0.01) whereas moderate to severe OHSS was significantly lower in the antagonist group (p<0.05). None of the patients had critical OHSS. Conclusions: GnRH antagonist Cetrorelix administration in early luteal phase in patients undergoing long or short protocol is effective in prevention and treatment of OHSS.